Paper vs. Digital Assessments: Evaluating Critical Thinking on Ecological Issues in Indonesian Madrasahs - Berlian, Zainal; Isnaini, Muhammad; Farwati , Ratna; Metafisika, Kartika; Velina, Yessy; Fitriyanni, Viona (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This research aims to determine the difference in the assessment results in the critical thinking skills of State Madrasah Ibtidaiyah (MIN) students or State Islamic schools in Indonesia using paper-based and digital-based tests. Data was collected from 314 participants representing MIN on four large islands in Indonesia, namely MIN Bogor Regency, West Java, MIN Sinjai Regency, South Sulawesi, MIN Palembang City, South Sumatra, and MIN Balikpapan City, East Kalimantan. The research method used a quantitative survey. A total of 24 valid Critical Thinking Skills Items with the Facione Critical Thinking Skills indicator as an instrument for measuring critical thinking skills. Factors such as motivation, technological accessibility, and effectiveness of test formats contribute to differences in results. This study provides new insights into the effectiveness of technology-based assessment in Madrasa education, especially in evaluating critical thinking skills. These findings lead to policy recommendations for improving the Madrasa assessment system in the digital era.